YUMMY Fast Food / Basyarah Rakhibi ... [et al.] - Rakhibi, Basyarah; Yaakob, Fathiyah; Mohd Safar, Fauziah; Ismail, Norsuhaila; Mohd Rosli, Norul Afidah (2003)
YUMMY Fast Food restaurant serves a variety of fast dishes to the customers. There are 3 main menus that are burger, hotdog and chicken chop. Besides that we are also have our special menu such as ' Banana Spilt' chicken grill and so on. In addition we also have combine our menu into special meal. We have 4 meals. They are, YUMMY Meal 1. YUMMY Meal 2, YUMMY Meal 3 and YUMMY Meal 4. YUMMY Fast Food restaurant is located at No. 174 , Jln Lagenda 1, 08000 Sungai Petani, Kedah. The target market for our business is mainly to the student, family and road user. We have been identified there are many schools, private college and other public and private institution there. There are also a lot of new housing that has been develop in Lagenda Heights. That will increase the number of our customer. Lastly in this executive summary, we hope that we are able to attract new customers to buy our product which have a quite similar to the other competitors such as KFC and Mc Donald.